A randomized, controlled comparison of different intensive lipid-lowering therapies in Chinese patients with non-ST-elevation acute coronary syndrome (NSTE-ACS): Ezetimibe and rosuvastatin versus high-dose rosuvastatin. (15th May 2017) - Ran, Dan; Nie, Hui-juan; Gao, Yu-lin; Deng, Song-bai; Du, Jian-lin; Liu, Ya-jie; Jing, Xiao-dong; She, Qiang
Abstract: Background: Statin combined with ezetimibe demonstrates significant benefit in lowering low density lipid cholesterol (LDL-C) and cardiovascular events abroad, but whether intermediate intensity statins combined with ezetimibe is superior to high-intensity statin monotherapy in Chinese people is unknown. Methods: A total of 125 patients were randomly assigned to a intermediate intensity rosuvastatin group (rosuvastatin 10 mg/d, n = 42), high-dose rosuvastatin group (rosuvastatin 20 mg/d, n = 41) or combination therapy group (ezetimibe 10 mg/d and rosuvastatin 10 mg/d, n = 42) with a 12-week follow-up. The primary end point was the proportion of patients who achieved the 2011 ESC/EAS LDL-C goal < 70 mg/dL (1.8 mmol/L) at week 12. Secondary end points included changes from baseline in lipids, the occurrence of all cardiovascular events, high-sensitivity C-reactive protein and safety markers. Results: The combination therapy group in the primary end point was significantly higher than rosuvastatin (20 mg) and rosuvastatin (10 mg) at week 12 (81.0% vs 68.3% vs 33.3%, P < 0.001). And the similar change was observed in reducing LDL-C levels at week 12 (67.28% vs 52.80% vs 43.89%, P < 0.001). The incidence of drug-related adverse events was much higher in the rosuvastatin 20 mg group than the rosuvastatin 10 mg group and the combination therapy group (17.0% vs 2.4% vs 4.8%, P < 0.05). Conclusions: The combination of rosuvastatin 10 mg/ezetimibe 10 mg was an effectively alternative therapy superior to rosuvastatin 20 mg or 10 mg with a greater effect on lowering LDL-C and a lower incidence of drug-related adverse events in Chinese patients.